Delivering Resilient Health Care - Hollnagel, Erik; Braithwaite, Jeffrey; Wears, Robert L.; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Health care is under tremendous pressure regarding efficiency, safety, and economic viability. It has responded by adopting techniques that have been useful in other industries, such as quality management, lean production, and high reliability - although with limited, and all-too-often disappointing, results. The Resilient Health Care Network (RHCN) has worked since 2011 to facilitate the interaction and collaboration among practitioners and researchers interested in applying concepts from resilience engineering to health care and patient safety. This has met with considerable success, not least because the focus from the start was on developing concrete ways to complement a Safety-I perspective with a Safety-II perspective.Building on previous volumes, Delivering Resilient Health Care presents documented experiences and practical guidance on how to bring Resilient Health Care into practice. It provides concrete advice on how to prepare a study, how to choose the right data, how to collect it, how to analyse the data, and how to interpret the results. This fourth book in the Resilient Healthcare series contains contributions from international experts in health care, organisational studies and patient safety, as well as resilience engineering. This book provides a practical guide for delivering resilient healthcare, particularly for clinicians on the frontline of care unsure how to incorporate resilience into their everyday work, managers coordinating care, and for policymakers hoping to steer the system in the right direction. Other groups - patients, the media, and researchers- will also find much of interest here.
1: Coming of Age;2: The Need of a Guide to Deliver Resilient Health Care;3: Procuring Evidence for Resilient Health Care;4: Resilience Engineering for quality improvement: Case study in a unit for the care of older people;5: Using workarounds to examine characteristics of resilience in action; 6: Simulation as a tool to study systems and enhance resilience; 7: Exploring resilience strategies in anaesthetists work: A case study using interviews and the Resilience Markers Framework (RMF); 8: Promoting resilience in the maternity services; 9: Team Resilience: Implementing resilient healthcare at Middlemore ICU; 10: Understanding normal work to improve quality of care and patient safety in a spine center; 11: Engineering resilience in an urban emergency department; 12: Patterns of adaptive behaviour and adjustments in performance in response to authoritative safety pressure regarding the handling of KCl concentrate solutions; 13: A case study of resilience in inpatient diabetes care; 14: Where process improvement meets resilience: a study of the preparation and administration of drugs in a surgical inpatient unit; 15: The Safety-II Case: Reconciling the gap between WAI and WAD through structured dialogue and reasoning about safety; 16: When Disaster Strikes: Sustained Resilience Performance in an Acute Clinical Setting; 17: Making it happen from research to practice
Includes bibliographical references and index.
Also available in print format.
Keywords: Social medicine; Medical care; Public health -- Social aspects; Delivery of Health Care; Health Services Administration; Quality Control; PSYCHOLOGY / Cognitive Psychology; accident; care; complexity; healthcare; health services; hospital; medical; patient safety; process improvement; reliability; resilience engineering; safety management; safety science; safety-ii.; workaround; Electronic books